Effect of Sodium Selenite and Zinc Sulphate on the Weight, Size, Seminal Fluid Traits, and Histological Changes of the Testis and Epididymis in Kurdi Rams - Palani, Zirak M. R.; Khalil, W.A; Kutaibani, Hamid E. I.; Amin, Faraidoon A. M. (CV. Literasi Indonesia, 2024)
This study was conducted to investigate the effects of Sodium selenite (Se) and zinc sulfate (Zn) supplementation individually and blended between them on semen quality, testicle size, weight, and Histological changes of the testis and epididymis, in 12 Kurdi rams. The twelve rams were divided randomly into 4 equal groups. The animals were divided into four groups 3 rams per group. The first group was the normal diet control without the addition of selenium and zinc, the second group added selenium (sodium selenite) at a concentration of 0.5 mg/kg fed, and the third group added zinc (zinc sulfate) at a concentration of 100 mg/kg fed. The fourth group added selenium with zinc at a concentration of 0.5 + 100 mg/kg fed and was given gelatin capsules daily for 90 days. Semen was collected on the 90th day of the experiment. The results showed that the level of Selenium and Zinc in the blood serum significantly (p≤0.05) increased the groups that added Se, Zn, and a combination of them compared to the control group. Overall results revealed that the abnormal sperms were improved by dietary selenium supplementation, No significant differences (P≥0.05) were found in semen volume, color, PH, sperm motility, sperm concentration, and percent live spermatozoa. Our conclusion from this study confirmed that the supplementation of Sodium selenite and zinc sulfate can improve semen quality and has positive effects on Histological parameters in Kurdi rams.